(untitled) (Hoboken, N.J., 2006)
Mergers and Acquisitions: A Global Tax GuideWhen a business engages in a multinational merger or acquisition, dealing with a diverse set of transaction-related tax rules is one of the major challenges to successful implementation. PricewaterhouseCoopers' Mergers and Acquisitions: A Global Tax Guide helps you navigate the complexities unique to these international deals. This invaluable guide focuses on the global tax aspects of mergers and acquisitions to provide you with the information you need to move the deal forward-under a variety of circumstances and in numerous markets. Presenting individual chapters for each of thirty-one countries, this essential handbook provides quick access to the tax information you need, and, as much as possible, reduces the effort required to compare the rules that apply in one jurisdiction with the rules that apply in others. Each country-specific chapter includes an overview of the general approaches to mergers and acquisitions taxation issues as well as detailed information about how the tax authorities in each country apply the rules to various aspects of a transaction.
Keywords: Consolidation and merger of corporations,International business enterprises; Taxation,Law and legislation,Taxation,Law and legislation